1995
DOI: 10.1161/01.atv.15.8.1219
|View full text |Cite
|
Sign up to set email alerts
|

Upregulation of Connexin43 Gap Junctions During Early Stages of Human Coronary Atherosclerosis

Abstract: Interactions between cells form the framework for understanding the pathogenesis of atherosclerosis, but little information is available on the role of direct intercellular communication via gap junctions in this process. To investigate gap junction expression in the pathogenesis of human atherosclerosis, lesions representing different stages of the disease were obtained from coronary arteries of hearts removed from patients undergoing cardiac transplantation. Twelve hearts, each providing 1 to 3 segments of a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
75
0

Year Published

1999
1999
2012
2012

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 115 publications
(78 citation statements)
references
References 38 publications
3
75
0
Order By: Relevance
“…The present findings refine the view suggested from previous studies 2,3,18,19 that high levels of Cx43 expression are associated with SMCs of a less contractile and more synthetic state, typically in an environment rich in extracellular matrix. These observations suggest that Cx43 gapjunctional intercellular communication may somehow be linked to the ability of SMCs to coordinate synthesis of extracellular matrix components, maintain the functional integrity of elastic media and/or regulate the repair and formation of the intima in vascular injury and disease.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…The present findings refine the view suggested from previous studies 2,3,18,19 that high levels of Cx43 expression are associated with SMCs of a less contractile and more synthetic state, typically in an environment rich in extracellular matrix. These observations suggest that Cx43 gapjunctional intercellular communication may somehow be linked to the ability of SMCs to coordinate synthesis of extracellular matrix components, maintain the functional integrity of elastic media and/or regulate the repair and formation of the intima in vascular injury and disease.…”
Section: Discussionsupporting
confidence: 91%
“…1 Recent evidence suggests that a further signaling mechanism, direct intercellular communication via gap junctions, may also participate in these interactions. 2,3 Gap junctions are clusters of transmembrane channels that link the cytoplasmic compartments of neighboring cells, allowing direct exchange of ions, second messengers, and small signaling molecules. The gap-junctional channel is constructed from a pair of hemichannels termed connexons, each connexon being assembled from 6 connexin molecules.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…It was formed that after the transformation of VSMC from differentiated contractile state to the activated synthetic state, the expression of Cx43 in VSMC increased sixfold and GJ diameter was enlarged (Inoguchi et al, 1995). Study showed that the expression of Cx43 at the thickened site of the endomembrane during early arteriosclerosis was highly elevated (Blackburn et al, 1995). Another study showed that Cx43 level is upregulated during the proliferation process of VSMC after the aorta was subjected to balloon injury or the animal was fed high-cholesterol diet (Polacek et al, 1997).…”
Section: Discussionmentioning
confidence: 99%
“…Sema domain, immunoglobulin domain, short basic domain, secreted, 3F (SEMA3F) is a member of the class 3 semaphorins and plays an important role in endothelial cell functions in vasculature (36). Inhibition of SEMA3F expression by small interfering RNA affected the intracellular localization and function of gap junction protein, ·1, 43 kDa which is expressed in medial smooth muscle cells of the normal vascular wall (37,38), being increased at early stages of atherosclerosis and reduced in advanced lesion (39).…”
Section: Discussionmentioning
confidence: 99%